OsIAA18, an Aux/IAA Transcription Factor Gene, Is Involved in Salt and Drought Tolerance in Rice - Feibing Wang (Frontiers Media S.A., 2021)
Auxin/indoleacetic acid (Aux/IAA) proteins play an important regulatory role in the developmental process of plants and their responses to stresses. A previous study has shown that constitutive expression of OsIAA18, an Aux/IAA transcription factor gene of rice improved salt and osmotic tolerance in transgenic Arabidopsis plants. However, little work is known about the regulatory functions of the OsIAA18 gene in regulating the abiotic stress tolerance of rice. In this study, the OsIAA18 gene was introduced into the rice cultivar, Zhonghua 11 and the OsIAA18 overexpression in rice plants exhibited significantly enhanced salt and drought tolerance compared to the wild type (WT). Moreover, overexpression of OsIAA18 in rice increased endogenous levels of abscisic acid (ABA) and the overexpression of OsIAA18 in rice plants showed hypersensitivity to exogenous ABA treatment at both the germination and postgermination stages compared to WT. Overexpression of OsIAA18 upregulated the genes involved in ABA biosynthesis and signaling pathways, proline biosynthesis pathway, and reactive oxygen species (ROS)-scavenging system in the overexpression of OsIAA18 in rice plants under salt and drought stresses. Proline content, superoxide dismutase (SOD), and peroxidase (POD) activities were significantly increased, whereas malonaldehyde (MDA), hydrogen peroxide (H2O2), and superoxide anion radical (O2–) content were significantly decreased in the transgenic plants under salt and drought stresses. Taken together, we suggest that OsIAA18 plays a positive role in drought and salt tolerance by regulating stress-induced ABA signaling. The OsIAA18 gene has a potential application in genetically modified crops with enhanced tolerance to abiotic stresses.